2024
DOI: 10.1002/ksa.12021
|View full text |Cite
|
Sign up to set email alerts
|

Derotational distal femoral osteotomy improves subjective function and patellar tracking after medial patellofemoral ligament reconstruction in recurrent patellar dislocation patients with increased femoral anteversion: A systematic review and meta‐analysis

Daofeng Wang,
Tong Zheng,
Yanwei Cao
et al.

Abstract: PurposeThe purpose of this study is to systematically review and quantitatively analyse the clinical outcomes of combined derotational distal femoral osteotomy (D‐DFO) and medial patellofemoral ligament reconstruction (MPFL‐R) in the treatment of recurrent patellar dislocation (RPD) with increased femoral anteversion angle (FAA).MethodsThis study was performed in line with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses) and AMSTAR (Assessing the Methodological Quality Of Systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Another, more recent systematic review of six studies investigating outcomes and satisfaction found very similar results but concluded that there is no consensus on when to perform a DeDFO [ 55 ]. A very recent meta‐analysis of 11 studies found a redislocation rate of 1.1% and overall excellent results, including better results when compared to isolated MPFL [ 49 ]. In the present study, which included 12 studies, the minimum cut‐off was 20° of anteversion, but some studies reported it as high as 30° [ 6 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another, more recent systematic review of six studies investigating outcomes and satisfaction found very similar results but concluded that there is no consensus on when to perform a DeDFO [ 55 ]. A very recent meta‐analysis of 11 studies found a redislocation rate of 1.1% and overall excellent results, including better results when compared to isolated MPFL [ 49 ]. In the present study, which included 12 studies, the minimum cut‐off was 20° of anteversion, but some studies reported it as high as 30° [ 6 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…These knees typically exhibit high-grade patellar mal-tracking, which may persist even after soft tissue reconstruction, resulting in the persistence of residual J-sign and an inability to define a favourable clinical outcome. Correction of these bony risk factors through osteotomy is deemed necessary [8,12,13,20,24,33]. Based on relatively large samples, this study describes the epidemiological characteristics of various bony structural abnormalities in knees with high-grade J-sign, aiming to facilitate precise preoperative assessment and guide intraoperative decision-making.…”
Section: Patellar J-sign and Bony Abnormalitiesmentioning
confidence: 99%
“…This leads to heightened medial patellofemoral ligament (MPFL) tension, increased stress on the lateral patella facet, and reduced stress on the medial patella facet [6,20]. Derotational distal femur osteotomy (DDFO) is the main surgical procedure for correcting enlarged femoral torsion in patients with patellar dislocation [12,13,23].…”
Section: Introductionmentioning
confidence: 99%
“…The FAA can guide the angle of rotational osteotomy. However, there is no consensus on the indications of DDFO in the treatment of recurrent patellar dislocation [10,23]. Kaiser et al [14], for example, believe that DDFO should be performed when the FAA exceeds 20°, whereas Zhang et al [27] believed that DDFO has good clinical results when the FAA exceeds 30°.…”
Section: Introductionmentioning
confidence: 99%